KERAGAMAN SERANGGA PADA TANAMAN KACANG KECIPIR (Psophocarpus tetragonolobus L.) di Bukit Kor, Marang, Terengganu - Permana, Mhd Agil; Hanif, Andini; Hashim, Nur Aida (Institute of Computer Science (IOCS), 2024)
Winged bean (Psophocarpus tetragonolobus L.) is a plant that is easy to cultivate in tropical areas. Pests in legume cultivation that damage legume crops are in the coleoptera, orthoptera, hemipteran groups. One of the main insects that can damage legume plants, including winged beans, is the sucking ladybug (Nezara viridula). The aim of this research is to determine the diversity of insects on winged bean plants (Psophocarpus tetragonolobus) in Kor Hill, Marang, Terengganu. The research method was carried out using qualitative methods, this research collected insects on winged bean cultivation plants. This research examines insect body parts, description and classification. The results of this research obtained fruit flies (Bactrocera cucurbitae), house flies (Hydrotaea), green planthoppers (Empoasca sp), koksi beetles (Coccinella transversalis), kerengga (Oecophylla smaragdina) and grasshoppers (Acrida cinerea).